Sustainable practices in lead acid battery recycling - Radja, Khatir (2025)
Recycling automotive batteries is a vital practice in the context of sustainability. Purchasing power in developing and emerging economies has increased dramatically over the past decades, especially when considering the proliferation of consumer cars worldwide. Consequently, the growing manufacturing volume of automotive batteries inevitably leads to increased battery waste, thus placing significant pressure on the sustainable development of human society. Recycling lead-acid batteries as a sustainable product is not only environmentally beneficial but also economically beneficial. A typical new lead-acid battery contains up to 80% recycled lead, and the plastic and battery components are also recyclable. When combined, almost all environmentally hazardous materials in the battery can be recycled. In this paper, we will study the recycling of lead-acid batteries used in fuel-powered cars. The results show that 54.4% of the metals in the battery, 28% of the plastics, and 17% of the liquids can be recycled, which provides materials for the manufacture of new batteries or for other uses.